Transfering of Meaning in the Modern Uzbek Poetry: Metaphors and Synecdoche - Isroilov, G`ayrat (FILOLOGIYA UFQLARI JURNALI, 2023)
Transfering of Meaning in the Modern Uzbek Poetry: Metaphors and Synecdoche